Pharmacotherapy Study Of Albendazole And Mebendazole For Soil Transmitted Helminths Infections In Children - Susanto, Inneke Kusumawati; William, William; Agatha, Nabila (Universitas Kristen Krida Wacana, 2024)
Soil Transmitted Helminths (STH) infection is a nematode infection of the intestine that requires soil for its transmission. The worms that cause Soil Transmitted Helminths infection include; Ascaris lumbricoides, Trichuris trichiura, hookworms (Necator americanus and Ancylostoma duodenale. The incidence of STH infection is quite high with the highest spread of STH infection in the child age group. Treatment of cases of STH infection is by administering antihelmintic drugs or worming drugs. Although there are four The drugs recommended by WHO, only the two drugs most often used in the treatment of STH infections, namely albendazole and mebendazole. Both drugs have been used for more than 30 years, but cases of STH infection still have a high incidence. That is why this literature review was written aims to describe the efficacy of the two drugs for STH infection in children so that their effectiveness can be assessed.The research method used was a literature review, a literature search was sourced from Proquest, Google scholar, Pubmed, Elsevier and Europe PMC. keywords Albendazole, Mebendazole, Soil Transmitted Helminths Infections, Children. There are 10 selected literatures to be studied in this literature review. The results showed that albendazole had satisfactory efficacy in STH infections caused by Ascaris lumbricoides and hookworms, but reduced efficacy in Trichuris trichiura worms. Mebendazole has satisfactory efficacy in STH infections caused by Ascaris lumbricoides and Trichuris trichiura, but reduced efficacy in hookworms. Albendazole and mebendazole does not cause side effects.